ANALISIS KEBERADAAN KOPERASI MAHASISWA (KOPMA) UNIVERSITAS RIAU - Ozi Zikri Amriadi; Sumarno '; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstack: The Student Student Cooperative is a cooperative whose members are students and are found in almost all public and private universities. In Riau University student cooperative experiencing adverse conditions, the presence of the University Students' Cooperative is less felt by the Riau Riau University Students. This study aims to see clearly the state of Riau University Student Cooperative is based on the activities undertaken by the organization of cooperatives, namely the Meeting of Members, managers and supervisors. This study used a qualitative approach. The data collection is done by observation, interviews, and documentation with the subject of management, supervisors, part of Student Affairs, and members of the University Students' Cooperative Riau as many as six people. Analysis of the data used is descriptive analysis with data collection measures, reduction, data display and conclusion. The results of the research are: 1) The meeting of members is still less than the maximum, for example, of the factors implementation, namely the lack of participants Meeting the members present, a total of 20 active members and a factor for membership, the ineffectiveness of membership status 2) the implementation the obligations of the board KOPMA UR there are some implementation of the obligations which is still not up, namely the inability the board is not in managing the organization and the cooperative efforts, 3) implementation of the regulatory obligations also could not be done optimally because of a lack resources supervisor, so that the supervisor can not perform their duties in a professional manner.Keywords: Existence, the Student Cooperative